2017
DOI: 10.1007/s11307-017-1049-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Folate-Derived Ga-68-Based PET Imaging Agent

Abstract: Purpose The folate receptor (FR) has emerged as an interesting diagnostic and therapeutic drug target with many potential applications in oncologic and inflammatory disorders. It was therefore the aim of this study to develop a folate-derived Ga-68-based positron emission tomography (PET) imaging tracer that is straightforward to radiolabel and could be broadly used in clinical studies. We validated its target binding affinity and specificity and compared it to [99mTc]EC20, the folate single-photon emission co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…However, Etarfolatide is a single-photon emission tomography (SPECT) tracer with limited imaging resolution and inferior quantification compared to positron emission tomography (PET). In pre-clinical studies, folatederived 68 Ga-based PET probe has shown slightly superior in vivo performance in comparison to Etarfolide [9]. This compound is to the best of our knowledge under investigation in humans in an inflammatory indication (NCT03494114) and currently not published in a peerreviewed journal.…”
Section: Introductionmentioning
confidence: 99%
“…However, Etarfolatide is a single-photon emission tomography (SPECT) tracer with limited imaging resolution and inferior quantification compared to positron emission tomography (PET). In pre-clinical studies, folatederived 68 Ga-based PET probe has shown slightly superior in vivo performance in comparison to Etarfolide [9]. This compound is to the best of our knowledge under investigation in humans in an inflammatory indication (NCT03494114) and currently not published in a peerreviewed journal.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an in vitro binding assay was performed with cell lines expressing different levels of FRα, as previously described [ 20 ]. One day prior to the in vitro experiment, the cells lines KB, OV90, and H2110, as well as A549 (each 1.0 × 10 6 cells per well, > 90% viability for each cell line) were seeded into 6-well plates containing growth medium (2.0 mL) and incubated at 37 °C to form subconfluent cell monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…All in vivo experiments were carried out in female, athymic nude mice (Envigo; outbread; 6–8 weeks, 20–25 g). Subcutaneous KB and OV90 xenografts (150 ± 20 mm 3 ) were established as previously described [ 5 , 20 ]. In detail, suspended KB cells (1.5 × 10 6 , viability > 93%) or suspended OV90 cells (1.0 × 10 7 , viability: > 95%) in a solution containing a 1:1 mixture of Matrigel (Becton Dickinson, Bedford, MA) and cell culture media (no FBS for OV90 xenografts) were subcutaneously inoculated on the right shoulder of anesthetized mice (1.5–2.0% isoflurane (Baxter Healthcare) in medical air (2 L/min)).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the nuclear imaging agents based on folic acid or pteroic acid [ 155 ] were developed for diagnosis of cancers overexpressing FR receptors such as breast, cervical, ovarian, colorectal, nasopharyngeal, renal, and endometrial cancers. Various 68 Ga-labelled agents demonstrated accumulation in cell cultures and mice bearing folate-receptor positive human nasopharyngeal carcinoma cell line (KB) xenografts [ 6 , 156 162 ]. [ 68 Ga]Ga-DOTA-PEG-FA comprising folic acid was investigated for the detection and quantification of inflammatory response to medical implants using mice with subcutaneously implanted polylactic acid and poly(N-isopropylacrylamide) particles as a model [ 60 ].…”
Section: Imaging Inflammationmentioning
confidence: 99%